Interdisciplinary challenges in the circular supply chains: A systematic literature review - Rasi, Raja Zuraidah; Ismail, Hazim; Shahbaz, Muhammad Saeed; Veera Pandiyan Kaliani Sundram, Veera Pandiyan Kaliani Sundram (ScienceDirect, 2023)
As the circular supply chain (CSC) gains traction in literature and practice, some academic groups are developing new fields that proceed from the CSC as a precisely technical concept. In order to examine the trends of CSC over time, to define how previous researchers have conceptualized the CSC ideology, and to identify the barriers to CSC adoption in businesses operations. This sys¬tematic review of the literature (n = 55) examines and discusses the disparate body of knowledge on supply chains (SCs). The paper claims that there are still differences across the circular economy (CE) definitions because of alleged antecedents and scopes, which has led to several research streams. However, CSC's goal remained the same: to encourage sustainable strategies that rejected the traditional linear paradigm that had harmed the environment. In order to be included in future practices and approaches, eight significant, interdisciplinary issues were discovered using SLR, along with the corresponding sub-challenges. These difficulties were dis¬cussed in this paper. Aiming to address the current concerns about balancing the environmental and economic perspectives, this study will provide guidelines to future researchers to identify the challenges from a real-world point of view by taking into account the social, environmental, and economic perspectives altogether.